Assessment for Learning: Changes in the Role of Assessment in Learning - Tatang Mulyana; Surti Kurniasih; Didit Ardianto (IJORER : International Journal of Recent Educational Research, 2021)
The purpose of this research is to describe the state of assessment for learning (AfL) in science learning. The research was conducted in February 2021. This research was conducted with a descriptive method using data collection techniques, namely a survey via google form. Before the instrument is used, calibration and testing are carried out and the test results of all items are declared valid and reliable. The results showed that the teacher agreed to the use of Assessment for Learning (AfL) in science learning, which could activate the learning process and accelerate the achievement of goals. In addition to the use of Assessment for Learning (AfL) in science learning, teachers also answered effectively in developing students' literacy skills according to subject coverage. Assesment for Learning (AfL) provides an overview of how students learn and achieve learning goals effectively that can be reported to students' parents. The obstacle in implementing assessment for learning (AfL) is that teachers still find it difficult to compile and develop assessment-based learning designs that are in accordance with process standards, so that most of these teachers adopt learning designs that are already available from various sources, so that the role of assessment is not yet a an integral part of the teaching and learning process.